Perancangan Interior âFive Sensesâ di Surabaya - Wulandari, Henny (Intra, 2015)
In the daily life, people interacts and shares information through their five senses. But people rarely realizes the importance of each senses, because they often use it unconsciously and because of less information updates. Where actually, the knowledge of five senses is more complex, can be an inspiration and can be developed in everyday life. Five Senses Recreation Center is an attractive, interactive, and educative five senses facility. Not only to learn about five senses, but also to consciously feel through five senses in games. This design uses the data collection and data analysis methods. The result of this design includes the games and interior design concept which supported by the layout, floor plan, ceiling plan, electrical mechanical, section, interior elements details, furniture details, and some interior perspective views.